Judgment in the presence of multiple conflicting anchors - Michael T. Bixter; Christian C. Luhmann (Acta Psychologica)
In uncertain environments, individuals often use external cues to guide their judgments and decisions. Anchoring refers to the finding that numerical judgments often gravitate towards previously considered standards. Although an extremely robust effect, prior research on anchoring largely focused on single-anchor paradigms. The present study instead investigated how multiple anchors affect numerical judgments. In Experiment 1, participants exposed to both a low and high anchor provided judgments that were between judgments made by participants exposed solely to low or high anchors. However, anchors that were encountered first exerted a disproportionate influence on subsequent judgments. Experiment 2 replicated this primacy effect both when anchors were plausible or implausible standards. Finally, Experiment 3 demonstrated that this primacy effect was reduced to non-significance by inserting a secondary distraction task following the exposure to each anchor. Implications of the current multiple-anchor results for various theories of anchoring effects are discussed.